Reporting multiple individual injuries in studies of team ball sports: A systematic review of current practice - Fortington, L. V.; van der Worp, H.; van den Akker-Scheek, I.; Finch, C. F. (Sports Medicine, 2017)
Background: To identify and prioritise targets for injury prevention efforts, injury incidence studies are widely reported. The accuracy and consistency in calculation and reporting of injury incidence is crucial. Many individuals experience more than one injury but multiple injuries are not consistently reported in sport injury incidence studies. Objective: The aim of this systematic review was to evaluate current practice of how multiple injuries within individuals have been defined and reported in prospective, long-term, injury studies in team ball sports. Data Sources: A systematic search of three online databases for articles published before 2016. Study Selection: Publications were included if (1) they collected prospective data on musculoskeletal injuries in individual participants; (2) the study duration was >1 consecutive calendar year/season; and (3) individuals were the unit of analysis. Data Extraction: Key study features were summarised, including definitions of injury, how multiple individual injuries were reported and results relating to multiple injuries. Results: Of the 71 publications included, half did not specifically indicate multiple individual injuries; those that did were largely limited to reporting recurrent injuries. Eight studies reported the number/proportion of athletes with more than one injury, and 11 studies presented the mean/number of injuries per athlete. Conclusions: Despite it being relatively common to collect data on individuals across more than one season, the reporting of multiple injuries within individuals is much more limited. Ultimately, better addressing of multiple injuries will improve the accuracy of injury incidence studies and enable more precise targeting and monitoring of the effectiveness of preventive interventions.